PERILAKU PENGERINGAN ROTAN MANAU (CALAMUS MANAN MIQ.) DAN ROTAN SEMAMBU (CALAMUS SCIPIONUM LOUR) - Efrida Basri; Suparman Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
Rattan is one of important minor forest products in Indonesia. In fact world supply of this material comes mainly from this country. One of the weaknesses of rattan is its susceptibility to various micro-organism specifically staining fungi and borer insects. The former flourishes when the moisture content of the cane is high. Immediate drying of rattan cane is therefore essential. Studies on the air drying and dehumidifying of two species of rattan canes have been undertaken, which include rate of drying and drying performance of the samples. As has been anticipated, the result shows that drying by dehumidifier is much faster compared with that of air drying. However, the quality of the two rattan species (degree of staining, insect attack, shrinkage, and colour) are about the same. The results also show that air drying rattans produces better gloss compared with that of dehumidifier drying. Other rattan defects due to drying speed such as shrinkage or wrinkle, were not noticeable.